The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1186/2040-2384-2-19
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum kallistatin levels in type 1 diabetes patients with vascular complications

Abstract: BackgroundKallistatin, a serpin widely produced throughout the body, has vasodilatory, anti-angiogenic, anti-oxidant, and anti-inflammatory effects. Effects of diabetes and its vascular complications on serum kallistatin levels are unknown.MethodsSerum kallistatin was quantified by ELISA in a cross-sectional study of 116 Type 1 diabetic patients (including 50 with and 66 without complications) and 29 non-diabetic controls, and related to clinical status and measures of oxidative stress and inflammation.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 44 publications
4
48
0
Order By: Relevance
“…6 In this study, the most common microvascular complication was microalbuminuria with an incidence of 31.7%. This was in agreement with Cohen-Bucay and Viswanathan 28 who reported that diabetic nephropathy affects approximately one-third of all people with diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…6 In this study, the most common microvascular complication was microalbuminuria with an incidence of 31.7%. This was in agreement with Cohen-Bucay and Viswanathan 28 who reported that diabetic nephropathy affects approximately one-third of all people with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these results, McBride et al 30 found a positive correlation between kallistatin and HbA1c in type 2 diabetes. Jenkins et al 6 found that kallistatin levels were higher in type 1 diabetic patients with hypertension and were significantly correlated with total cholesterol and LDL as well as renal function. The correlation between kallistatin and inflammation among the studied population supports other studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations